SEISMICITY AND KINEMATIC EVOLUTION OF MIDDLE EGYPT - Badawy A.; Abdel-Monem S.M.; Sakr K.; Ali Sh.M. (My University, 2006)
Based on historical and instrumental seismicity as well as recent GPS measurements, the seismicity and kinematic evaluation of middle Egypt is presented. Middle Egypt suffered in historical times by six major earthquakes and the Ramses II temple on the west bank of the Nile in Luxor, was almost destroyed by an ancient event. The temporal distribution of recent earthquakes (1900-1997) is highly scattered with only nine events recorded. Only after the installation of the modern Egyptian national seismograph network (ENSN) the seismic record of middle Egypt increased with a total of 280 earthquakes from 1998 to 2004. Focal mechanism solutions of the largest five events during the ENSN's operation period reveal reverse faulting mechanism with minor strike-slip component on the west bank of the Nile, while a normal faulting mechanism dominate in the eastern side. The orientations of both P- and T-axes are consistent with the Red Sea-Gulf of Suez stress field. Dynamic source parameters of these five events were derived from P-wave spectra as well. Three campaigns of GPS measurements were carried out for the middle Egypt network that established after the first instrumental earthquake on 14 December 1998 in this area. The velocity vectors for each epoch of observations were calculated and deformation analysis was performed. The horizontal velocity varies between 1 and 4 mm/year across the network. The deformation pattern suggests significant contraction across the southeastern sector of the study area while, the northwestern part is characterized by an extension strain rates. High shear strain is observed along the epicenteral area of the Mw = 4.0 June 2003 earthquake possibly reflecting the stress accumulation stage of a seismic cycle. © 2006 Elsevier Ltd. All rights reserved.
Keywords: FOCAL MECHANISM; GPS; KINEMATICS; MIDDLE EGYPT; NILE VALLEY; SEISMICITY; SOURCE PARAMETERS